GENDER FEATURES OF INTERACTION HORMONAL ACTIVITY ADIPOSE TISSUE AND PROINFLAMMATORY STATUS IN HYPERTENSION WITH METABOLIC SYNDROME - I. D. Bespalova; N. V. Ryazantseva; V. V. Kalyuzhin; I. A. Osikhov; B. Yu. Murashev; Yu. A. Medyantsev; V. A. Rudnitsky (Бюллетень сибирской медицины)
Objective: research gender features of relationship of hormonal activity of adipose tissue and proinflammatory status with essential hypertension (EH) in combination with metabolic syndrome (MS).Material and methods. Were examined 46 patients with essential hypertension stage (BP < 180/110 mm Hg.) in conjunction with the metabolic syndrome. Along with a complete clinical, laboratory and instrumental examination adopted in specialized cardiological clinic, were defined concentrations in serum leptin, adiponectin, resistin and visfatin and the level of markers of systemic inflammation (C-reactive protein, neopterin and fibrinogen), was assessed the level of spontaneous production of cytokines and active oxygen species and the expression level of CD4, CD8 and CD36 – blood mononuclear leukocytes markers.Results and conclusions. It was established that the hormonal status of adipose tissue have women with EH combined with MS are characterized by higher levels of leptin and adiponectin in blood serum than in men.It was established not only a significant role adipokin imbalance in mechanisms of MS and systemic inflammation in these patients category, but also were studied gender characteristics. While for men in the development of the above pathological manifestations hipoadiponektinemia has the most meaning, and for women – hyperleptinemia.